Emerging Directions in Emotional Episodic Memory - Dolcos, Florin; Katsumi, Yuta; Weymar, Mathias; Moore, Matthew; Tsukiura, Takashi; Dolcos, Sanda (Frontiers in Psychology, 2017)
Building upon the existing literature on emotional memory, the present review examines emerging evidence from brain imaging investigations regarding four research directions: (1) Social Emotional Memory, (2) The Role of Emotion Regulation in the Impact of Emotion on Memory, (3) The Impact of Emotion on Associative or Relational Memory, and (4) The Role of Individual Differences in Emotional Memory. Across these four domains, available evidence demonstrates that emotion- and memory-related medial temporal lobe brain regions (amygdala and hippocampus, respectively), together with prefrontal cortical regions, play a pivotal role during both encoding and retrieval of emotional episodic memories. This evidence sheds light on the neural mechanisms of emotional memories in healthy functioning, and has important implications for understanding clinical conditions that are associated with negative affective biases in encoding and retrieving emotional memories.